A novel modular opto-biomechatronics bioreactor for simultaneous isotropic mechanical stretch application and fluorescence microscopy under cell and tissue culture conditions - Merten, Anna-Lena; Schöler, Ulrike; Lesko, Christian; Kreiß, Lucas; Schneidereit, Dominik; Linsenmeier, Fabian; Stolz, Axel; Rappl, Sebastian; Ali, Mohamed; Potié, Tim; Ahmed, Adel; Morales-Dalmau, Jordi; et al. (Biosensors and Bioelectronics: X, 2024)
Mechanical stresses are an environmental challenge virtually all tissues in the body are exposed to and thus, are of fundamental interest to study cell reactions in mechanobiology. Yet, unlike acute short-term mechanical cell stimulations, long-term or cyclic mechano-stimulation as experienced in the body is difficult to reproduce. Bioreactors are designed to control cell culture conditions, but still, there are yet no technical solutions available to merge bioreactor and opto-biomechatronics technologies for cyclic stretch-applications and simultaneous live cell imaging. To close this gap, we have engineered an opto-biomechatronics module, consisting of our in-house developed IsoStretcher technology and customised epifluorescence optics, into an automated bioreactor platform. For this, redesigned polydimethylsiloxane (PDMS) chambers with closed geometry (∽700 μL internal volume) to warrant sterile operation were developed. Those chambers could be flushed with cell solution for cell seeding in a sterile manner. The epifluorescence imaging module was engineered into the reactor underneath the IsoStretcher to allow for continuous image acquisition during long-term stretch cycles (hours to days). The system was validated on human fibroblast BJ foreskin cells, and Cal-520 Ca2＋ fluorescence was stably imaged using our in-built autofocus functionality. Cultures for 24 h within the IsoStretcher-bioreactor preserved a normal cell morphology as compared to external incubator control cultures. Isotropic stretch was reliably transferred to the cell membranes. Our system with in-built bioreactor and opto-biomechatronics functionality provides a holistic technology platform for the growing field of mechanobiology to allow long-term observations of cultured single cells and confluent cell layers that are subjected to cyclic long-term isotropic stretch protocols.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Automation; Bioreactor; Cell stretching device; Mechanosensitive ion channels; Mechanotransduction